Copper-catalyzed synthesis of 2, 2, 2-trifluoroethyl selenoethers and their insecticidal activities. Issue 47 (22nd November 2018) - Dong, Jingnan; Li, Zhengyu; Weng, Zhiqiang
Abstract : A copper-catalyzed synthesis of aryl or alkyl 2, 2, 2-trifluoroethyl selenoethers was developed. Some of them exhibited promising insecticidal activities against tetranychus cinnabarinus . Abstract : A simple and efficient protocol for the copper-catalyzed synthesis of aryl or alkyl 2, 2, 2-trifluoroethyl selenoethers has been developed. This reaction proceeded smoothly in the presence of CuI/phen as the catalyst, with elemental selenium, 1, 1, 1-trifluoro-2-iodoethane, and NaBH4 as reagents in DMF with a broad scope of functionalized (hetero)aryl or alkyl halides. Different functional groups were tolerated and moderate to excellent yields of 2, 2, 2-trifluoroethyl selenoethers were obtained. Some of the synthesized compounds exhibited promising insecticidal activities.